Literature Review: The Relationship between Tea Consumption Habits and the Incidence of Anemia in Pregnant Women - Azizatullatifah, Safira; Sarbini, Dwi (Jurnal Kesehatan, 2024)
Introduction: There was an increase in the prevalence of anemia among pregnant women by 11.8% from 2013 to 2018 in Indonesia. The habit of drinking tea is one of the factors associated with anemia in pregnant women due to the presence of tannins in tea that can inhibit the absorption of iron in the body. This literature study aims to examine the relationship between tea drinking habits and the incidence of anemia in pregnant women. Method: Articles were searched through Google Scholar with the keywords "tea drinking habits, anemia, pregnancy", and "relationship, tea consumption, anemia, pregnant women", as well as "relationship, tea consumption habits, anemia, pregnant women". The inclusion criteria used were articles from 2013 to 2023, full text in Indonesian, cross-sectional research methods, research subjects namely anemic or non-anemic pregnant women and indexed by SINTA S1-S4. Based on these inclusion criteria, a total of 10 articles were reviewed.  Results: Analysis of respondent characteristics showed that 50% of the articles had a respondent age of 20-35 years, 40% of the articles had a gestational age of trisemester II, and 40% of the articles had parity ≥2 children. 50% of the articles showed that pregnant women rarely/never consumed tea and 40% of the articles showed that pregnant women experienced anemia. As many as 7 articles (70%) stated that there was a relationship between tea consumption habits and the incidence of anemia in pregnant women, while 3 articles (30%) stated that there was no relationship between tea consumption habits and the incidence of anemia in pregnant women. Conclusion: There is a relationship between tea consumption habits and the incidence of anemia in pregnant women. Pendahuluan: Terjadi peningkatan prevalensi anemia pada ibu hamil sebesar 11,8% dari tahun 2013 sampai dengan tahun 2018 di Indonesia. Kebiasaan minum teh menjadi salah satu faktor yang berhubungan dengan anemia pada ibu hamil dikarenakan kandungan tanin pada teh yang dapat menghambat penyerapan zat besi dalam tubuh. Studi pustaka ini bertujuan untuk mengkaji hubungan kebiasaan minum teh dengan kejadian anemia pada ibu hamil. Metode: Artikel ditelusuri melalui Google Scholar dengan kata kunci “kebiasaan minum teh, anemia, kehamilan”, dan “hubungan, konsumsi teh, anemia, ibu hamil”, serta “hubungan, kebiasaan konsumsi teh, anemia, ibu hamil”. Kriteria inklusi yang digunakan adalah artikel tahun 2013 sampai dengan tahun 2023, teks lengkap berbahasa Indonesia, metode penelitian cross-sectional, subjek penelitian yaitu ibu hamil anemia atau tidak anemia, dan terindeks SINTA S1-S4. Berdasarkan kriteria inklusi tersebut, sebanyak 10 artikel ditelaah. Hasil: Analisis karakteristik responden menunjukkan bahwa 50% artikel memiliki usia responden 20-35 tahun, 40% memiliki usia kehamilan trimester II, dan 40% memiliki paritas ≥2 anak. Sebanyak 50% artikel menunjukkan ibu hamil jarang/tidak pernah mengonsumsi teh, dan 40% menunjukkan ibu hamil mengalami anemia. Sebanyak 7 artikel (70%) menyatakan adanya hubungan antara kebiasaan konsumsi teh dengan kejadian anemia pada ibu hamil. Sebagai perbandingan, sebanyak 3 artikel (30%) menyatakan tidak ada hubungan antara kebiasaan konsumsi teh dengan kejadian anemia pada ibu hamil. Kesimpulan: Ada hubungan antara kebiasaan konsumsi teh dengan kejadian anemia pada ibu hamil.